2007
DOI: 10.1128/aac.00454-06
|View full text |Cite
|
Sign up to set email alerts
|

Posaconazole Plasma Concentrations in Juvenile Patients with Invasive Fungal Infection

Abstract: Posaconazole is an orally bioavailable triazole antifungal agent for the treatment and prophylaxis of invasive fungal infection. We evaluated plasma posaconazole concentration data from juvenile (younger than 18 years; n ‫؍‬ 12) and adult (18 to 64 years; n ‫؍‬ 194) patients who participated in a multicenter, phase 3, open-label study that assessed the efficacy and safety of posaconazole treatment for persons who were intolerant of or had invasive fungal infection refractory to standard antifungal therapies. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
94
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(108 citation statements)
references
References 30 publications
10
94
0
4
Order By: Relevance
“…In healthy volunteers, age, gender, and race or ethnicity do not have a clinically relevant effect on the pharmacokinetics of posaconazole (30). Similar plasma posaconazole concentrations have been observed in adult and pediatric patients with IFIs (18).…”
mentioning
confidence: 55%
“…In healthy volunteers, age, gender, and race or ethnicity do not have a clinically relevant effect on the pharmacokinetics of posaconazole (30). Similar plasma posaconazole concentrations have been observed in adult and pediatric patients with IFIs (18).…”
mentioning
confidence: 55%
“…Several studies with febrile patients with neutropenia and/or invasive fungal infections have shown that when PSC is administered at the recommended dosage of 400 mg orally twice daily, the resulting human serum PSC levels are generally Ͻ1 g/ml (10,11,21). In a previous study with mice infected with R. microsporus (18), the serum PSC levels at 40 mg/kg were similar (Ͻ1 to 2 g/ml) to those obtained with the drug administered at the recommended dosage in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Posaconazole has been used as an alternative to AmB in treatment of S. vasiformis infections because of the toxicity of AmB (319,334) or in combination with other antifungals (Table 4) (162). Posaconazole's safety profile for children under the age of 13 years is limited (174,334).…”
Section: Vol 24 2011 Mucormycosis Caused By Unusual Mucormycetes 429mentioning
confidence: 99%